Description of a new genus and five new species of earthworms (Oligochaeta, Lumbricidae) - Mršić, Narcis (Scopolia, 1987)
Opisan je novi rod Meroandriella g. n. in pet novih vrst deževnikov: Meroandriella dinarica n. g., sp. n., Alpodinaridella (Alpodinaridella) lozniciana sp. n., Aporrrectodea papukiana sp. n., Aporrectodea pannoniella sp.n. in Aporrectodea bohiniana sp. n.
Keywords: deževniki; Oligochaeta; Lumbricidae; zoologija; zoology